Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. Issue 1 (December 2017) - Joshi, Peter; Pirastu, Nicola; Kentistou, Katherine; Fischer, Krista; Hofer, Edith; Schraut, Katharina; Clark, David; Nutile, Teresa; Barnes, Catriona; Timmers, Paul; Shen, Xia; Gandin, Ilaria; et al.
Abstract Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606, 059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 andLPA ). We also validate previous suggestions thatAPOE, CHRNA3/5, CDKN2A/B, SH2B3 andFOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan. Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.